Investimento social privado: discussão sobre o papel das fundações na gestão das políticas sociais - Maillard, Nathalie de Amorim Perret Gentil Dit (2010)
This paper aims to study the corporate foundations and the objective is to discuss their role in social policies management. The study is motivated because foundations have been assuming a prominent role as social policies agents, not just for the resources available, but also for its inclusion in the policies management by their projects. Firstly, foundations were designated just to execute social actions, today they are seen as strategic organizations, able to effect a more sustainable management and increase the dialogue between business and community. Therefore, foundations implement and generate social projects in order to enable better living conditions for poor people and ensure their social rights - right to health, education, housing and other essential terms. It should be emphasized there isn´t a withdrawal of state policymaker and funder role in social policies, on the contrary, the state expanded its functions of planning, assessment and control, ensuring citizens' right to access quality life. To achieve our objective, we provide a literature review on the transformation of state, enterprises and Third Sector roles. The research methodology is qualitative and quantitative interviews were conducted in 6 large and active corporate foundations in education area. The study showed there is a conscious concern from foundations to social problems and several projects are carried out to combat these. There is also an attempt to contribute to state, even if not fully aligned with government programs. The foundations contribute to state but there is no way yet to assess the real impact because the absence of similar indicators, also the dialogue between the sectors is fragile, so the exchange and sharing of skills and knowledge is still small